Identification of new metribuzin-tolerant wheat (Triticum spp.) genotypes - Bhoite, R.; Si, P.; Stefanova, Katia; Siddique, K.; Yan, G. (CSIRO Publishing, 2017)
© CSIRO 2017. Herbicide-tolerant wheats are preferred for effective weed management. Rapid phenotyping and effective differential dose are vital for the identification of tolerant genotypes among large quantities of genetic resources. A sand-tray system has been developed to enable rapid assessment of metribuzin damage in wheat seedlings. In total, 946 wheat genotypes were evaluated for metribuzin tolerance by using this system under control and metribuzin-treated conditions. SPAD chlorophyll content index (CCI) offered a non-destructive and rapid analysis of leaf chlorophyll content in wheat seedlings. The application rate for 50% reduction in SPAD CCI (I50) was 3.2-fold higher in the current tolerant genotype (Eagle Rock) than the susceptible genotype Spear. A confirmed dose of 800g a.i. ha-1 could differentiate between metribuzin-tolerant and -susceptible lines. The experimental design with two-directional blocking followed by statistical analysis to model the spatial variation was instrumental in selecting potential tolerant or susceptible genotypes. Metribuzin reduced chlorophyll by 51.4% in treated seedlings. The overall adjusted mean SPAD CCI ranged from 13.5 to 42.7 for control (untreated) plants and from 0.1 to 29.9 for treated plants. Through repeated validation, nine genotypes had higher chlorophyll content after metribuzin treatment and significantly (P < 0.05) outperformed the tolerant Eagle Rock, whereas 18 genotypes had significantly (P < 0.05) higher chlorophyll reduction than the susceptible Spear. The top five tolerant and susceptible genotypes were selected for a genetic study of metribuzin tolerance. Domesticated forms of tetraploid and hexaploid wheats had higher tolerance to metribuzin, which suggests that the level of domestication and higher ploidy level contributes to metribuzin tolerance. The new sources of tolerance will accelerate breeding for metribuzin tolerance.